Comparison of body composition between two elite women's volleyball teams - Maly, T.; Mala, L.; Zahalka, F.; Balas, J.; Cada, M. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2011)
In sport and in top performance sport in particular, the continuous monitoring of body composition (BC) may regulate the training process, affecting positively athletes' top form. BC is, therefore, considered to be one of the components of the physical fitness of athletes. Research studies dealing with BC in women volleyball players are often focused on a lower performance level when compared with the submitted study. The problem in the field of results comparison is with the variety in the methodology used in BC assessment. OBJECTIVE: The objective of our study is to describe the body composition (BC) profile of top performance women volleyball players and verify whether there are differences in the chosen parameters between them. The examined group consists of women volleyball players of two teams which were participants in the European Champions League (T1, n = 12; T2, n = 9). METHODS: By means of multifrequency bioimpedance analysis, we observed Lean Body Mass (LBM), Fat Mass (FM), Body Cell Mass (BCM), relative BCM (BCMrel), ExtraCellular Mass (ECM) and their mutual ratio (of ECM/ BCM), Cell Quote (CQ), phase angle (a), Basal Metabolic Rate (BMR), Total Body Water (TBW) while making a distinction between ExtraCellular (ECW) and IntraCellular (ICW) Water. One-way ANOVA and Cohen's d were used for the comparison of differences between the monitored teams. RESULTS: Differences in the examined parameters of body composition between the screened samples were not statistically significant (p > 0.05). Effect size revealed moderate differences for other parameters (a, ECM, BCM, ECM/ BCM, BMR, FM and CQ). Fat mass percentage in our women players was lower in comparison to values recorded in women players in most other studies. The relatively high values of TBW, LBM and ECM/BCM in women volleyball players of both teams indicate their good performance capacity. CONCLUSIONS: The body composition profile revealed the appropriate predispositions of the observed players for their performance in volleyball. The measured parameters of BC corresponding to top performance sport are better than in high performance sport or in the general population. Our values of BC in elite women volleyball players can serve as standards for other athletes attempting to achieve international level.